ChemInform Abstract: Distinct Reactivity of Morita—Baylis—Hillman Acetates as a Novel C2 Component in Amine‐Catalyzed [2 + 2 + 2] and [2 + 4] Annulations. Issue 33 (25th July 2013) - Chen, Rongshun; Xu, Silong; Wang, Liyi; Tang, Yuhai; He, Zhengjie
Abstract The preparation of substituted cyclohexanes (III) by a DABCO‐catalyzed [2 + 2 + 2] annulation of acetates (I) with dinitriles (II) is reported.